Pengaruh Green Marketing Terhadap Minat Beli Pada Produk Fore Coffee Di Bandung - Amalia, Sofiatunnisa; Ramli, Rosmini (JURNAL ILMIAH EDUNOMIKA, 2024)
The objective of this study is to investigate the influence of various components of the green marketing mix. Specifically, green product, green price, green place, and green promotion on the purchase intentions of Fore Coffee in Bandung City. The data utilized in this research, sourced from 100 consumers who have previously engaged in transactions at Fore Coffee outlets in Bandung, underwent rigorous testing for validity, reliability, and classical assumptions. Employing purposive sampling, data collection was executed, and subsequent analysis was conducted using multiple linear regression facilitated by the Statistical Package for the Social Sciences (SPSS). Of the five hypotheses examined, empirical evidence supported three. The empirical findings suggest that the attributes of green product and green place positively correlate with purchase intentions, while no substantial impact was observed in relation to green price and green promotion. However, when considered collectively, these factors collectively influence purchase intentions. Further exploration by future researchers may uncover additional direct influencers of purchase intentions. The implications of this study's outcomes extend to the strategic planning of Fore Coffee's management and analogous industries, offering guidance on how to enhance the quality of these attributes to better align with consumer purchase intentions.